Dual Antitubercular and Antileishmanial Profiles of Quinoxaline Di-N-Oxides Containing an Amino Acidic Side Chain - Juan F. González; María-Auxiliado; Lena Huck; José María Orduña; Francisco Bolás-Fernández; Elena de la Cuesta; Nazia Haseen; Ashraf Ali Mohammed; J. Carlos Menéndez (MDPI AG, 2024)
We present a new category of quinoxaline di-N-oxides (QdNOs) containing amino acid side chains with dual antituberculosis and antileishmanial activity. These compounds were synthesized by combining a regioselective 2,5-piperazinedione opening and a Beirut reaction and were screened for their activity against Mycobacterium tuberculosis and the promastigote and amastigote forms of representative species of the Leishmania genus. Most QdNOs exhibited promising antitubercular activity with IC50 values ranging from 4.28 to 49.95 μM, comparable to clinically established drugs. Structure-activity relationship analysis emphasized the importance of substituents on the aromatic ring and the side chain. Antileishmanial tests showed that some selected compounds exhibited activity comparable to the positive control miltefosine against promastigotes of Leishmania amazonensis and Leishmania donovani. Notably, some compounds were found to be also more potent and less toxic than miltefosine in intracellular amastigote assays against Leishmania amazonensis. The compound showing the best dual antitubercular and leishmanicidal profile and a good selectivity index, 4h, can be regarded as a hit compound that opens up new opportunities for the development of integrated therapies against co-infections.